Short communication: administering an appeasing substance to Bos indicus-influenced beef cattle at weaning and feedlot entry. (22nd October 2019) - Cooke, R. F.; Millican, A.; Brandão, A. P.; Schumaher, T. F.; de Sousa, O. A.; Castro, T.; Farias, R. S.; Cappellozza, B. I.
Abstract : The bovine appeasing substance (BAS ) is expected to have calming effects in cattle experiencing stressful situations. Therefore, this study investigated the impacts of BAS administration during two of the most stressful events within beef production systems: weaning and feedlot entry. In experiment 1, 186 Bos indicus- influenced calves (73 heifers, 113 bulls) were weaned at 211 ± 1 days of age (day 0). At weaning, calves were ranked by sex and BW, and assigned to receive BAS (Nutricorp, Araras, SP, Brazil; n = 94) or water (CON ; n = 92). Treatments (5 ml) were topically applied to the nuchal skin area of each animal. Calf BW was recorded and samples of blood and tail-switch hair were collected on days 0, 15 and 45. Calves that received BAS had greater ( P < 0.01) BW gain from day 0 to 15 compared with CON. Overall BW gain (days 0 to 45) and BW on days 15 and 45 were also greater ( P ≤ 0.03) in BAS v. CON. Plasma haptoglobin concentration was less ( P < 0.01) in BAS v. CON on day 15, whereas cortisol concentrations in plasma and tail-switch hair did not differ between treatments ( P ≥ 0.13). In experiment 2, 140 B. indicus- influenced bulls (∼27 months of age) from 2 different pasture-based systems (70 bulls/origin) were transported to a commercial feedlot (≤ 200-km transport; day -1). On day 0, bulls were ranked by source and BW, and assigned to receive BAS ( n = 70) or CON ( n = 70) and the same sampling procedures as in experiment 1. Bulls receiving BAS had greater ( P = 0.04) BW gain from day 0 to 15, but less ( P < 0.01) BW gain from day 15 to 45 compared to CON. No other treatment effects were detected ( P > 0.14). Therefore, BAS administration to beef calves alleviated the haptoglobin response associated with weaning, and improved calf growth during the subsequent 45 days. Administration of BAS to beef bulls at feedlot entry improved BW gain during the initial 15 days, but these benefits were not sustained throughout the 45-day experiment.